‘Connecting the dots’ for generating a momentum for Universal Health Coverage in Bangladesh: findings from a cross-sectional descriptive study - Nahitun Naher; Syed Masud Ahmed; Lal B Rawal; Tarek Hossain (BMJ Open)
Objective This study was conducted to explore how and whether, the strategic grants made by the Rockefeller Foundation (RF) in different sectors of health systems in the inception phase were able to ‘connect the dots’ for ‘generating a momentum for Universal Health Coverage (UHC)’ in the country.Design Cross-sectional descriptive study, using document review and qualitative methods.Setting Bangladesh, 17 UHC-related projects funded by the RF Transforming Health Systems (THS) initiative during 2010–2013.Data Available reports of the completed and on-going UHC projects, policy documents of the government relevant to UHC, key-informant interviews and feedback from grant recipients and relevant stakeholders in the policy and practice.Outcome measures Key policy initiatives undertaken for implementing UHC activities by the government post grants disbursement.Results The RF THS grants simultaneously targeted and connected the academia, the public and non-profit development sectors and news media for awareness-building and advocacy on UHC, develop relevant policies and capacity for implementation including evidence generation. This strategy helped relevant stakeholders to come together to discuss and debate the core concepts, scopes and modalities of UHC in an attempt to reach a consensus. Additionally, experiences gained from implementation of the pilot projects helped in identifying possible entry points for initiating UHC activities in a low resource setting like Bangladesh.Conclusions During early years of UHC-related activities in Bangladesh, strategic investments of the RF THS initiative played a catalytic role in sensitising and mobilising different constituencies for concerted activities and undertaking necessary first steps. Learnings from this strategy may be of help to countries under similar conditions of ‘low resource, apparent commitment, but poor governance,’ on their journey towards UHC.